METHODS OF ADMINISTERING R-KETAMINE - KELLY, Terence Alfred; MATHEWS, Maju; JUMAA, Mouhannad (2024)
The disclosure provides a method of treating or ameliorating depressive symptoms of a subject, comprising administering a therapeutically effective amount of a composition comprising R(-)-ketamine, or a pharmaceutically acceptable salt thereof, to the subject. La divulgation concerne une méthode de traitement ou d'amélioration des symptômes dépressifs d'un sujet, comprenant l'administration au sujet d'une quantité thérapeutiquement efficace d'une composition comprenant de la R(-)-kétamine, ou un sel pharmaceutiquement acceptable de celle-ci.